ULECTOMY AS A SURGICAL OPTION IN PRIMARY HEALTH CARE: CASE REPORT - Henrique Moura Fonsêca dos Santos, Álvaro; Almeida Avelino Cintra, Anistein; Gabrielly de Souza Moura, Camila; Ferreira Bernardo, Leilane; da Rocha Costa, Maurício (Health and Society, 2023)
Introduction: One of the clinical challenges that comprises the phase of mixed dentition in pediatric patients is tooth impaction. This alteration has a multifactorial etiopathology, with local and systemic factors being related. When tooth eruption does not occur spontaneously, the dentist can perform a surgical procedure, called ulectomy, in order to allow a free path for the tooth to come to occupy its position in the dental arch. Objective: To present ulectomy as a surgical option for the treatment of dental impaction in Primary Health Care. Case report: A 6-year-old female patient came with her parents to the Basic Health Unit in the city of Lajedo-PE, complaining of delayed eruption of permanent teeth. The intraoral clinical examination revealed the absence of elements 11 and 21 and the presence of a thick layer of gingival tissue. The most indicated therapeutic approach was the ulectomy technique. Intraoral and extraoral antisepsis were performed; application of topical anesthetic; infiltrative terminal anesthesia; and elliptical incisions promoting removal of the coronary cap. Hemostasis was promoted by tamponade and no postoperative prescription was required. The patient returned in 15 days, and the onset of eruption of elements 11 and 21 was observed. Conclusion: Ulectomy can be considered a conservative, safe and effective therapeutic method for the resolution of prolonged retention of dental elements in pediatric dentistry. Due to the safety of the procedure, it can be performed in Primary Health Care, as a way of guaranteeing its principles, as long as there is sufficient technical and scientific knowledge to do so.